Concept of sustainable development: regulatory aspect - E. I. Mayorova; E. V. Temnova (Управление)
The paper considers the concept of sustainable development that has been shaped under the influence of the planetary ecological crisis associated with the increasing anthropogenic impact on the environment and awareness of progressive mankind of the need for developing a new, non-anthropocentric, approach to environmental management and nature in general. The authors perform a historical review of the origin and development of the concept of sustainable development as it appears in the international regulatory documents that reverberate the decisions on changing the course of the entire world community from technogenic to sustainable development. The study highlights the contribution of proposals to the legislation of the Russian Federation to take joint actions in order to promote the “green economy” with the Constitution of the Russian Federation dwelling upon the environmental articles, e.g. the major legislation of the environmental law On Environmental Protection adopted recently, and a number of codes to ensure nature management scoping the regulations for environmental and legal responsibility. According to the Russian experts, the transition to sustainable development in each country and in the same country throughout history may have different priorities, which is reflected in the legislation. In particular, the Government has approved the Strategy for Sustainable Development of Rural Areas of the Russian Federation for the period up to 2030. Currently, the legislation dwells upon the prevailing anthropocentric trends, but when the idea of sustainable development reaches the critical mass, a transition from the consumer worldview to a respectful and friendly attitude of humans to nature where they belong seems hopeful.